Endosidin2-14 Targets the Exocyst Complex in Plants and Fungal Pathogens to Inhibit Exocytosis. Issue 3 (9th May 2019) - Huang, Lei; Li, Xiaohui; Li, Yang; Yin, Xianglin; Li, Yong; Wu, Bin; Mo, Huaping; Liao, Chao-Jan; Mengiste, Tesfaye; Guo, Wei; Dai, Mingji; Zhang, Chunhua
Abstract : Endosidin2-14 shows potential as a small molecule chemical inhibitor as it targets EXO70, a subunit of the exocyst complex, resulting in inhibition of exocytosis in plants and fungal pathogens. Abstract: The evolutionarily conserved octameric exocyst complex tethers secretory vesicles to the site of membrane fusion during exocytosis. The plant exocyst complex functions in cell wall biosynthesis, polarized growth, stress responses, and hormone signaling. In fungal pathogens, the exocyst complex is required for growth, development, and pathogenesis. Endosidin2 (ES2) is known to inhibit exocytosis in plant and mammalian cells by targeting the EXO70 subunit of the exocyst complex. Here we show that an analog of ES2, ES2-14, targets plant and two fungal EXO70s. A lower dosage of ES2-14 than of ES2 is required to inhibit plant growth, plant exocytic trafficking, and fungal growth. ES2-14 treatments inhibit appressorium formation and reduce lesion sizes caused by Magnaporthe oryzae . Inhibition of EXO70 by ES2-14 in Botrytis cinerea also reduces its virulence in Arabidopsis ( Arabidopsis thaliana ). Interestingly, ES2-14 did not affect EXO70 localization or transferrin recycling in mammalian cells. Overall, our results indicate that a minor change in ES2 affects its specificity in targeting EXO70s in different organisms and they demonstrate the potential of using ES2-14 to study the mechanisms of plant and fungal exocytosis and the roles of exocytosis in fungus-plant interactions.